Implementation of Lean Instruments in Ceramics Industries - Ulewicz, Robert; Kleszcz, Daniel; Ulewicz, Małgorzata (Management systems in production engineering, 2021)
The article presents the results of the research on the level of implementation of Lean instruments in the ceramics industry. The research was carried out in ceramic factories in Poland and Germany. Based on the results obtained, the most commonly used Lean instruments in the ceramics industry were defined. The dependence of the use of Lean instruments on the size of the enterprise was also determined. It was established that the Lean activities undertaken in the ceramics industry are focused solely on the implementation of individual methods and tools, without a pre-defined goal. This approach in the ceramics industry is ineffective, but unfortunately it is most often used in the implementation of the Lean philosophy, especially in small ceramics enterprises.